Comparison of Preoperative Counselling Versus Control on Anxiety Symptoms in Patients Undergoing Surgery Under General Anesthesia - Khan, Zafar Ullah; Faqooq, Umar; Ahmed Tariq, Sheikh Muhammad; Butt, Muhammad Muazzam; Iqbal Butt, Muhammad Umer; Qureshi, Ahmed Masood (Biological and Clinical Sciences Research Journal, 2025)
Preoperative anxiety is common among surgical patients, often leading to adverse psychological and physiological outcomes. Improving perioperative counseling may help reduce anxiety, particularly in healthcare settings where communication gaps and misconceptions about anesthesia are prevalent. Objective: To compare the effect of structured preoperative counseling combined with standard counseling versus standard counseling alone on anxiety symptoms in patients undergoing surgery under general anesthesia. Methods: This randomized controlled trial included 150 elective surgical patients aged 20–75 years with ASA I–II status at Hameed Latif Hospital, Lahore. Participants were randomized through lottery into two equal groups. Group A received structured counseling in addition to routine nursing-led counseling, while Group B received standard preoperative counseling alone. Anxiety was assessed one hour prior to surgery using Zung’s Self-Rating Anxiety Scale (SAS). Data were analyzed using SPSS version 21, with independent sample t-tests applied at a significance level of p < 0.05. Age and gender stratification were performed to explore subgroup differences. Results: The mean anxiety score in Group A was significantly lower (49.24 ± 14.87) compared with Group B (61.25 ± 15.02) (p = 0.000). Anxiety reduction remained statistically significant across most age categories except in the 51–65 year group. Both male and female patients demonstrated lower anxiety levels after structured counseling compared to standard counseling alone. Conclusion: Structured preoperative counseling significantly reduced anxiety scores among surgical patients compared to standard counseling, demonstrating its potential to improve perioperative psychological wellbeing. Enhanced communication may be particularly valuable in settings where patients experience heightened procedural apprehension.